A risk-based approach to forecasting component obsolescence. (December 2021) - Mastrangelo, Christina M.; Olson, Kara A.; Summers, Dennis M.
Abstract: Prediction of electronic component obsolescence is a critical aspect of managing diminishing manufacturing sources and materials shortages (DMSMS). Systems with intended long operating lifetimes combined with shorter market-driven lifetimes of components therein drive the need for obsolescence management. This work defines and describes a Weibull-based conditional probability method, a risk-based approach to predicting microelectronic component obsolescence. The conditional probability method is used to determine the likelihood of a component becoming obsolete within a specified forecast horizon given that the component is still procurable at the time of analysis. The method is compared to a mean time to failure (MTTF)-based approach with a case study using a ten-year retrospective analysis. The case study demonstrates the viability of the conditional probability method and shows overall improved accuracy especially for more recent analysis periods. A risk-based approach also better enables component-to-component comparison which can help prioritize DMSMS efforts. Highlights: A Weibull-based conditional probability method is defined and described. The method is a risk-based approach to predicting electronic component obsolescence. A case study is presented using linear regulators. Results are comparable or better than a mean time to failure-based approach.